Crude protein level of the diet on blood urea nitrogen in alpaca and sheep - Huamán, Mariela (2023)
The study aimed to evaluate the effect of dietary crude protein (CP) on blood urea nitrogen (BUN) in alpacas and sheep. Four male alpacas (53 ± 5 kg) and four male sheep (24 ± 4 kg) were used in an experimental design of overchange with a 4x4 Latin square arrangement (4 animals, 4 periods and 4 treatments). The diets contained 7, 10, 13 and 16% CP and were made from alfalfa meal, oat straw and a commercial supplement of minerals and vitamins. Feed was offered ad libitum. Each period had an adaptation stage (10 d) and an evaluation stage (4 d) and the animals were in individual pens. A linear regression was performed between the levels of N in the diet (independent variable) and the levels of BUN (dependent variable) for each species, comparing the intercept and the slope between both by means of t-Student. In both species, BUN increased with the level of CP in the diet (p<0.05). Alpacas with a low level of CP in the diet presented higher levels of BUN than sheep (p<0.05); however, sheep showed a greater increase in BUN per unit of CP in the diet (p<0.05). It is concluded that, although there is a direct relationship between BUN and CP levels in the diet in both species, the rates of increase are different between them.